Soft-scape quality issues in landscape construction industry : Malaysia - Ab Sani, Jasasikin; Ahmad Sharip, Nur Athirah; Ibrahim, Putri Haryati (Universiti Putra Malaysia, 2020)
Over the past decade, concerns have been expressed on the quality of construction products and processes. Massive developments experienced by the construction sector in Malaysia have led to a devastating compromise in quality. The problems in a construction project are mainly related to quality such as building does not comply with specifications, and sub-standard still exists. Attainment of an acceptable level of quality in construction has long been a problem. Landscape construction, in general, is part of the total construction and is not exempted from the same problem. In general, all of them refer to quality as conformance or compliance with the specification. Landscape construction can be part of an overall construction project or independent landscape project. Therefore, the objective of quality standard in landscape construction may not be different from the purpose of quality standard in total construction. Thus, this research aims to evaluate the softscape quality issues in Malaysia. This research is looking at the responses given by the relationship between status, types of organisations, groups of organisations and gender with the problems of quality of softscape construction work. The survey respondents were among Landscape Architects from various landscape organisations who were landscape consultants, landscape contractors, developers, government agencies, and educational institutions. The findings of the research are about the issue of landscape quality management in Malaysia in general. Majority of the respondents pointed out that the quality of the softscape construction in Malaysia was not properly controlled. Responses from the survey have shown the level of dissatisfaction of respondents on softscape quality in Malaysia.